The CLEO-database: Nine forested headwater streams in Sweden, 1977-2009. - Temnerud, Johan; Andersson, L.; Arheimer, Berit; Bishop, Kevin; Bringmark, Lage; Lundin, Lars; Löfgren, Stefan; Moldan, Filip; Nilsson, Torbjörn (Swedish University of Agricultural Sciences, 2026)
***The CLEO project database***

The dataset contains data from the research project 'CLEO - CLimate change and Environmental Objectives'. It's aim was to investigate how climate change affects the ability to meet the environmental goals set for 2020. The project sought to answer the following questions: "How should the next generation of environmental targets for 2050 be formulated in view of climate change, changes in land use and the disposal of pollutants?" and "How should strategies for reducing emissions be developed so that we maximize synergies in order to achieve the environmental targets?". The project was conducted at SLU starting in 2010 and ending in 2015. It was financed by the Swedish Environmental Protection Agency and carried out in collaboration with IVL Swedish Environmental Research Institute, SMHI Swedish Meteorological and Hydrological Institute, and Lund University. The CLEO database was put together by SLU in collaboration with SMHI and published on SLU's website in 2015. In 2026 the data and documentation for CLEO was moved to Researchdata.se.

To achieve the goals of CLEO related to runoff chemistry from the Swedish forested landscape, a uniquely comprehensive database of water quality together with supporting climate and catchment information has been created.

At the center of this database are 9 well-studied forest catchments where the CLEO water quality modelling effort has been focused. The data for these streams was derived from Integrated Monitoring (IM) programme, which is part of SLU's environmental monitoring and assessment. This has resulted in an ensemble of simulations decades back in time and predictions decades into the future.

Furthermore, a database that includes runoff, chemistry, climate, and associated catchment GIS information has been compiled for another 215 larger catchments from national and regional monitoring programs.

The information (observed and modelled) of the 9 reference catchments as well as of the 215 larger streams and rivers are made publicly available below.

A detailed overview of all data included in the CLEO-database can be found in the documentation file "information-to-data.pdf".

The file "translation-table---database.xlsx" containing explanations for common abbreviations used in the datafiles.

The data is split into 10 zipped folders.

Data for the 9 reference catchments is stored in the folders:

**catchment_information.zip (1.16 MB)**
The file contains four files providing information on the nine catchments.

- Map of Sweden.jpg: 84 KB; Map of the location of the 9 sites in Sweden
- maps-soil-sampling-location-topography.ppt: 918 KB; Maps with information on soil, topography, bedrock, sampling locations from Kindla, Aneboda and Gårdsjön
- svartberget-catchment.pptx: 559 KB; Maps with information on catchment, vegetation and soil from Svartberget
- catchment-information---database1.xlsx: 11 KB; Various catchment information for all sites, e. g. program, geographic location, different codes, X, Y, N, E, overview vegetation (partly information in Swedish)

**hydrology.zip (548 KB)**
- Observed runoff (runoff-for-all-sites---database.xls, 2 Mb)

Runoff observed
Site, timeperiod:

Gårdsjön F1, 1979 - 2009
Gårdsjön G2, 1992 - 2005
Berg (Pipbäcken Nedre), 1985 - 2008
Aneboda, 1997 - 2008
Stubbetorp (Dammen), 1985 - 1997
Kindla, 1997 - 2008
Sniptjärn, 1977 - 1997
Ammarnäs skog (Lillbäcken), 1985 - 2000
Svartberget, 1981 - 2008

**chemistry.zip (1.28 MB)**
- Observed stream chemistry (vattenkemi-cleo-prio-1--database.xlsx, 2 Mb)

Site, time period:

Gårdsjön F1, 1989 - 2009
Gårdsjön G2, 1989 - 2009
Berg (Pipbäcken Nedre), 1984 - 2009
Aneboda, 1996 - 2009
Stubbetorp (Dammen), 1983 - 1997
Kindla, 1994 - 2009
Sniptjärn, 1976 - 2008
Ammarnäs skog (Lillbäcken), 1984 - 2000
Svartberget, 1986 – 2009

**climate.zip (56 Mb)**
- Modelled PTHBV precipitation and temperature (1961-2009) for all sites (precipitation_temperature-pthbv.xlsx, 3 Mb)
- Daily relative humidity (RH) and wind speed data for all sites from different climate stations (rhwind-speed-cleo-prio1---database.xls, 8 Mb)
- Daily precipitation, wind speed, global radiation, air temperature, air humidity and wind direction data from 'Mast station' at Gårdsjön, site Gårdsjön F1, Gårdsjön G2 and Aneboda (gardsjon_aneboda-meteorological-data---database.xls, 4,1 Mb)
- Hourly values of different solar radiation parameters from various climate stations (sol-radiation-files---database.xlsx, 52 Mb)

**deposition.zip (514 Kb)**
- deposition (deposition_database.xlsx, 528 Kb)

Deposition observed/modelled
OF = open field deposition, TF = throughfall deposition

Site, frequency, OF time series, TF time series:

MATCH model, annual, - , 2006-2008
Gårdsjön, annual/monthly, OF 1996-2008, TF 1996-2008
Berg, monthly, OF 1983-2004
Aneboda, monthly, OF 1983-2008, TF 1996-2005
Kindla, monthly, OF, 1996-2008, TF 1996-2005
Ammarnäs, monthly, 1983-2009+1991-2000, TF 1991-2009
Svartberget, monthly, OF 2002-2007, TF 1983-1997

**soil.zip (2.25 Mb)**
- Soil/ water temperature, moisture and groundwater level data: Aneboda, Gardsjön and Kindla (soil_water-temp_groundwater_streamwater-level---database.xlsx, 1.26 Mb)
- Soil chemistry data: Aneboda, Kindla and Gardsjön file (soil-chemistry-aneboda-kindla-gardsjon_database.xls, 205 Kb)
- Soil physics data: Aneboda and Kindla (soil-physics-aneboda-kindla---database1.xls, 89 Kb)
- Soil water (SW) chemistry data: Aneboda and Kindla (soil-water-chemistry---database.xls, 1 Mb)
- Ground water (GW) chemistry data: Aneboda and Kindla (ground-water-chemistry---database.xls, 895 Kb)
Detailed information on SW and GW sampling locations and depths: Aneboda, Kindla and Gardsjön (details-to-groundwater-and-soilwater-sampling.doc, 97 Kb)

Note: Soil data files above may contain some inconsistencies

Soil data from the S-transect: Svartberget (1995):
- Soil parameters and background information of the sampling sites: Svartberget (soil-chemistry-svartberget---database.doc, 126 Kb)
- Loss on Ignition (s-transect-svartberget---database.xls, 162 Kb)
- Hydr. Conductivity (hydr-conductivity-svartberg---database.xls, 42 Kb)
- Particle size distribution (particle-size-svartberget---database.xls, 138 Kb)
- pF-curve (pf-curve-svartberget---database.xls, 97 Kb)

**litterfall.zip (10 Kb)**
- Yearly litterfall chemistry data from 1998-2009 for Aneboda and Kindla (litterfall_yearlychemistry----database.xls, 28 Kb)

**vegetation.zip (39.5 Mb)**
All files contain a comprehensive explanation of column headings. Years when inventories were carried out are specified. Moreover, Aneboda, Gårdsjön, and Kindla maps are included within the files where data from these catchments are available.

- Algae and lichens on young spruce - Aneboda, Gårdsjön, and Kindla (01algae_and_lichens_on_young_spruce-cleo_database.xlsx, 5.5 Mb)
- Circular plots: Soil - Aneboda, Gårdsjön, and Kindla (02circular_plots_soil-cleo_database.xlsx, 5.5 Mb)
- Circular plots: Trees - Ammarnäs, Aneboda, Gårdsjön, and Kindla (03circular_plots_trees-cleo_database.xlsx, 6.5 Mb)
- Circular plots: Trees (basal area) - Ammarnäs and Gårdsjön (04circular_plots_trees_basal_area-cleo_database.xlsx, 2.6 Mb)
- Circular plots: Trees (small trees) - Ammarnäs and Gårdsjön (05circular_plots_trees_small_trees-cleo_database.xlsx, 2.6 Mb)
- Circular plots: Vegetation layers - Ammarnäs, Aneboda, Gårdsjön, and Kindla (06circular_plots_vegetation_layers-cleo_database.xlsx, 6.0 Mb)
- Intensive plots: Trees - Ammarnäs, Aneboda, Gårdsjön, and Svartberget (07intensive_plots_trees-cleo_database.xlsx, 5.1 Mb)
- Intensive plots: Understorey vegetation - Ammarnäs, Aneboda, Gårdsjön, Kindla, and Svartberget (08intensive_plots_understorey_vegetation-cleo_database.xlsx, 6.2 Mb)
- Forest damage - Gårdsjön and Kindla (09forest_damage-cleo_database.xlsx, 3.3 Mb)
- Tree cover on intensive plots - Aneboda, Gårdsjön, and Kindla (10tree_cover_on_intensive_plots-cleo_database.xlsx, 5.5 Mb)
- Epiphytes on tree trunks - Ammarnäs, Gårdsjön, and Svartberget (11epiphytes_on_tree_trunks-cleo_database.xlsx, 66 kb)

** 215_streams_and_rivers.zip (131 Mb)**
- S-Hype modelled daily runoff for all sites (1990-2010) (runoff-s-hype-all-sites---database.xlsx, 70 MB)
- Various monthly collected parameters for all sites (1990-2010) (water-chemistry-all-sites---database.xlsx, 5,4 MB)
- PTHBV modelled daily temperature and precipitation for all sites (1990-2010) (precipitation-and-temperature-all-sites---database.xlsx, 62 MB)
- Information regarding location, soil type, and land use; and some statistics from chemical, hydrological, and climatic variables for all sites (catchment-information---database.xlsx, 321 KB)
- Map with location of all 215 sites within Sweden (overviewmap_sites215.jpg, 55 KB)

***CLEO-projektets databas***

Datasetet innehåller data från forskningsprojektet ”CLEO – CLimate change and Environmental Objectives”. Syftet var att undersöka hur klimatförändringarna påverkar möjligheten att uppnå de miljömål som satts upp för 2020. Projektet försökte besvara följande frågor: ”Hur bör nästa generations miljömål för 2050 formuleras med tanke på klimatförändringarna, förändringar i markanvändningen och hanteringen av föroreningar?” och ”Hur bör strategier för att minska utsläppen utvecklas så att vi maximerar synergierna för att uppnå miljömålen?”. Projektet genomfördes vid SLU med start 2010 och slut 2015. Det finansierades av Naturvårdsverket och genomfördes i samarbete med IVL Miljöforskning, SMHI och Lunds universitet. CLEO-databasen sammanställdes av SLU i samarbete med SMHI och publicerades på SLU:s webbplats 2015. År 2026 flyttades data och dokumentation för CLEO till Researchdata.se.

För att uppnå CLEO:s mål avseende kemiska avrinningar från det svenska skogslandskapet har en unik och omfattande databas över vattenkvalitet skapats, tillsammans med kompletterande information om klimat och avrinningsområden.

I centrum för denna databas finns nio välstuderade skogsavrinningsområden där CLEO:s modellering av vattenkvaliteten har fokuserats. Uppgifterna för dessa vattendrag hämtades från programmet Integrated Monitoring (IM), som ingår i SLU:s miljöövervakning och miljöbedömning. Detta har resulterat i en samling simuleringar som sträcker sig flera decennier tillbaka i tiden och prognoser som sträcker sig flera decennier framåt i tiden.

Dessutom har en databas som innehåller information om avrinning, kemi, klimat och tillhörande avrinningsområden i GIS sammanställts för ytterligare 215 större avrinningsområden från nationella och regionala övervakningsprogram.

Informationen (observerad och modellerad) om de nio referensavrinningsområdena samt de 215 större vattendragen och floderna är tillgänglig för allmänheten nedan.

En detaljerad översikt över all data som ingår i CLEO-databasen finns i dokumentationsfilen "information-to-data.pdf.

Filen "translation-table---database.xlsx" innehåller förklaringar till vanliga förkortningar som används i datafilerna.

Data är uppdelad i 10 zippade mappar.

Data för de 9 referensavrinningsområdena lagras i mapparna:

**catchment information.zip (1.16 MB)**
- Karta över de 9 platserna i Sverige: (Map of Sweden.jpg, 84 kb)
- Kartor med information om jordmån, topografi, berggrund, provtagningsplatser från Kindla, Aneboda och Gårdsjön (maps-soil-sampling-location-topography.ppt, 918 Kb)
- Kartor med information om avrinningsområde, vegetation och mark från Svartberget (svartberget-catchment.ppt, 559 Kb)
- Olika uppgifter om avrinningsområden för alla platser, t.ex. program, geografisk plats, olika koder, X, Y, N, E, översikt över vegetation (delvis information på svenska) (catchment-information---database1.xlsx, 11 Kb)

**hydrology.zip (548 KB)**
- Observerad avrinning (runoff-for-all-sites---database.xls, 2 Mb)

Observerad avrinning
Plats, tidsperiod:

Gårdsjön F1, 1979–2009
Gårdsjön G2, 1992–2005
Berg (Pipbäcken Nedre), 1985–2008
Aneboda, 1997–2008
Stubbetorp (Dammen), 1985–1997
Kindla, 1997–2008
Sniptjärn, 1977–1997
Ammarnäs skog (Lillbäcken), 1985–2000
Svartberget, 1981–2008

**chemistry.zip (1,28 MB)**
- Observerad vattendragskemi (vattenkemi-cleo-prio-1--database.xlsx, 2 Mb)

Plats, tidsperiod:

Gårdsjön F1, 1989–2009
Gårdsjön G2, 1989–2009
Berg (Pipbäcken Nedre), 1984–2009
Aneboda, 1996–2009
Stubbetorp (Dammen), 1983–1997
Kindla, 1994–2009
Sniptjärn, 1976–2008
Ammarnäs skog (Lillbäcken), 1984–2000
Svartberget, 1986–2009

**climate.zip (56 Mb)**
- Modellerad PTHBV-nederbörd och temperatur (1961–2009) för alla platser (precipitation_temperature-pthbv.xlsx, 3 Mb)
- Dagliga data för relativ luftfuktighet (RH) och vindhastighet för alla platser från olika klimatstationer (rhwind-speed-cleo-prio1---database.xls, 8 Mb)
- Dagliga data för nederbörd, vindhastighet, global strålning, lufttemperatur, luftfuktighet och vindriktning från ”Mast station” vid Gårdsjön, platsen Gårdsjön F1, Gårdsjön G2 och Aneboda (gardsjon_aneboda-meteorological-data---database.xls, 4,1 Mb)
- Timvärden för olika solstrålningsparametrar från olika klimatstationer (sol-radiation-files---database.xlsx, 52 Mb)

**deposition.zip (514 Kb)**
- deposition (deposition_database.xlsx, 528 Kb)

Observerad/modellerad deposition
OF = deposition i öppet fält, TF = genomfallande deposition

Plats, frekvens, OF-tidsserie, TF-tidsserie:

MATCH-modell, årlig, - , 2006–2008
Gårdsjön, årlig/månatlig, OF 1996–2008, TF 1996–2008
Berg, månadsvis, OF 1983–2004
Aneboda, månadsvis, OF 1983–2008, TF 1996–2005
Kindla, månadsvis, OF, 1996–2008, TF 1996–2005
Ammarnäs, månadsvis, 1983-2009+1991-2000, TF 1991-2009
Svartberget, månadsvis, OF 2002-2007, TF 1983-1997


**soil.zip (2,25 Mb)**
- Data om mark-/vattentemperatur, fuktighet och grundvattennivå: Aneboda, Gardsjön och Kindla (soil_water-temp_groundwater_streamwater-level---database.xlsx, 1,26 Mb)
- Data om markens kemi: Aneboda, Kindla och Gardsjön (soil-chemistry-aneboda-kindla-gardsjon_database.xls, 205 Kb)
- Data om markens fysik: Aneboda och Kindla (soil-physics-aneboda-kindla---database1.xls, 89 Kb)
- Jordvattenkemi (SW): Aneboda och Kindla (soil-water-chemistry---database.xls, 1 Mb)
- Grundvattenkemi (GW): Aneboda och Kindla (ground-water-chemistry---database.xls, 895 Kb)
Detaljerad information om provtagningsplatser och djup för SW och GW: Aneboda, Kindla och Gardsjön (details-to-groundwater-and-soilwater-sampling.doc, 97 Kb)

Observera: Jorddatafilerna ovan kan innehålla vissa inkonsekvenser.

Jorddata från S-transsekten: Svartberget (1995):
- Jordparametrar och bakgrundsinformation om provtagningsplatserna: Svartberget (soil-chemistry-svartberget---database.doc, 126 Kb)
- Förlust vid förbränning (s-transsekt-svartberget---database.xls, 162 Kb)
- Hydr. konduktivitet (hydr-conductivity-svartberg---database.xls, 42 Kb)
- Partikelstorleksfördelning (particle-size-svartberget---database.xls, 138 Kb)
- pF-kurva (pf-curve-svartberget---database.xls, 97 Kb)

**litterfall.zip (10 Kb)**
- Årliga kemiska data för lövfall från 1998–2009 för Aneboda och Kindla (litterfall_yearlychemistry----database.xls, 28 Kb)


**vegetation.zip (39,5 Mb)**
Alla filer innehåller en utförlig förklaring av kolumnrubrikerna. Åren då inventeringarna genomfördes anges. Dessutom ingår kartor över Aneboda, Gårdsjön och Kindla i filerna där data från dessa avrinningsområden finns tillgängliga.

- Alger och lavar på ung gran - Aneboda, Gårdsjön och Kindla (01algae_and_lichens_on_young_spruce-cleo_database.xlsx, 5,5 Mb)
- Cirkulära ytor: Jord - Aneboda, Gårdsjön och Kindla (02circular_plots_soil-cleo_database.xlsx, 5,5 Mb)
- Cirkulära ytor: Träd - Ammarnäs, Aneboda, Gårdsjön och Kindla (03circular_plots_trees-cleo_database.xlsx, 6,5 Mb)
- Cirkulära plotar: Träd (basalarea) – Ammarnäs och Gårdsjön (04circular_plots_trees_basal_area-cleo_database.xlsx, 2,6 Mb)
- Cirkulära ytor: Träd (små träd) – Ammarnäs och Gårdsjön (05circular_plots_trees_small_trees-cleo_database.xlsx, 2,6 Mb)
- Cirkulära ytor: Vegetationsskikt – Ammarnäs, Aneboda, Gårdsjön och Kindla (06circular_plots_vegetation_layers-cleo_database.xlsx, 6,0 Mb)
- Intensiva ytor: Träd - Ammarnäs, Aneboda, Gårdsjön och Svartberget (07intensive_plots_trees-cleo_database.xlsx, 5,1 Mb)
- Intensiva ytor: Undervegetation – Ammarnäs, Aneboda, Gårdsjön, Kindla och Svartberget (08intensive_plots_understorey_vegetation-cleo_database.xlsx, 6,2 Mb)
- Skogsskador – Gårdsjön och Kindla (09forest_damage-cleo_database.xlsx, 3,3 Mb)
- Trädtäcke på intensiva ytor – Aneboda, Gårdsjön och Kindla (10tree_cover_on_intensive_plots-cleo_database.xlsx, 5,5 Mb)
- Epifyter på trädstammar – Ammarnäs, Gårdsjön och Svartberget (11epiphytes_on_tree_trunks-cleo_database.xlsx, 66 kb)

** 215_streams_and_rivers.zip (131 Mb)**
- S-Hype-modellerad daglig avrinning för alla platser (1990–2010) (runoff-s-hype-all-sites---database.xlsx, 70 MB)
- Olika månatliga insamlade parametrar för alla platser (1990–2010) (water-chemistry-all-sites---database.xlsx, 5,4 MB)
- PTHBV-modellerad daglig temperatur och nederbörd för alla platser (1990–2010) (precipitation-and-temperature-all-sites---database.xlsx, 62 MB)
- Information om läge, jordtyp och markanvändning samt vissa statistiska uppgifter om kemiska, hydrologiska och klimatiska variabler för alla platser (catchment-information---database.xlsx, 321 kB)
- Karta med läget för alla 215 platser i Sverige (overviewmap_sites215.jpg, 55 kB)
CLEO-databasen: Nio skogsklädda källflöden i Sverige, 1977–2009.
Keywords: WATERSHED CHARACTERISTICS; SURFACE WATER CHEMISTRY; water chemistry; environmental monitoring; miljöövervakning; Hydrography; Hydrografi; soil types; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Environment; Miljö; Inland Waters; Sjöar och vattendrag